Characterization of Putative Iron Responsive Genes as Species-Specific Indicators of Iron Stress in Thalassiosiroid Diatoms - Whitney, LeAnn P.; Lins, Jeremy J.; Hughes, Margaret P.; Wells, Mark L.; Chappell, Phoebe D.; Jenkins, Bethany D. (Frontiers in Microbiology, 2011)
Iron (Fe) availability restricts diatom growth and primary production in large areas of the oceans. It is a challenge to assess the bulk Fe nutritional health of natural diatom populations, since species can differ in their physiological and molecular responses to Fe limitation. We assayed expression of selected genes in diatoms from the Thalassiosira genus to assess their potential utility as species-specific molecular markers to indicate Fe status in natural diatom assemblages. In this study, we compared the expression of the photosynthetic genes encoding ferredoxin (a Fe-requiring protein) and flavodoxin (a Fe-free protein) in culture experiments with Fe replete and Fe stressed Thalassiosira pseudonana (CCMP 1335) isolated from coastal waters and Thalassiosira weissflogii (CCMP 1010) isolated from the open ocean. In T. pseudonana, expression of flavodoxin and ferredoxin genes were not sensitive to Fe status but were found to display diel periodicities. In T. weissflogii, expression of flavodoxin was highly responsive to iron levels and was only detectable when cultures were Fe limited. Flavodoxin genes have been duplicated in most diatoms with available genome data and we show that T. pseudonana has lost its copy related to the Fe-responsive copy in T. weissflogii. We also examined the expression of genes for a putative high affinity, copper (Cu)-dependent Fe uptake system in T. pseudonana. Our results indicate that genes encoding putative Cu transporters, a multi-Cu oxidase, and a Fe reductase are not linked to Fe status. The expression of a second putative Fe reductase increased in Fe limited cultures, but this gene was also highly expressed in Fe replete cultures, indicating it may not be a useful marker in the field. Our findings highlight that Fe metabolism may differ among diatoms even within a genus and show a need to validate responses in different species as part of the development pipeline for genetic markers of Fe status in field populations.